UNILATERAL UTERINE HORN ADHESION IN A CROSSBRED HEIFER - S. Prakash; S. Raja; V. Prabaharan; S. Satheshkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A Jersey crossbred heifer was presented to the Gynaecology Unit of Veterinary Clinical Complex, Veterinary College and Research Institute, Orathanadu for pregnancy diagnosis. Rectal examination revealed rigid cervix and flaccid uterine horns. Further examination revealed that left uterine horn was adhering with the adnexa like a firm mass and unable to retract. However, the right uterine horn and both the ovaries were free of adhesions and were easily movable. Ultrasonographic examination revealed left uterine horn was curled and there was synechiae as evidenced by dense hyperechoic bands around the contours of left uterine horn which confirm the unilateral left uterine horn adhesion.